Therapy of chronic heart failure in patients with hypersensitivity pneumonitis and coronary heart disease - A. V. Medvedev; G. E. Alichubanova; N. G. Dem'yanenko; S. A. Kasimtseva; M. N. Kovalevskaya; R. V. Tarasov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Objective: to study the effect of enalapril and valsartan + sacubitril on the reduction of CHF symptoms, on the change in functional and radiological parameters in patients with hypersensitivity pneumonitis (HP) combined with coronary heart disease. Materials and methods. 183 patients with hypersensitivity pneumonitis were examined: 88 patients with coronary artery disease and 95 patients without it. CHF was diagnosed in 39 (44.3%)% of CHD patients and in 13 (13.68%) "isolated" SHG. General clinical, instrumental and functional study methods were performed in each group. When assessing the effectiveness of CHF treatment, patients are divided into two groups: еnalapril was prescribed to 20 patients in the main group: 21 patients in the comparison group received valsartan + sacubitril. Results. 24-week therapy allowed to reduce the manifestations of diastolic dysfunction: a decrease in the indexed end-systolic volume of the left atrium by 5.13% in the main and 11.2% in the group, comparisons;, end-diastolic volume of the left ventricle by 4.13 and 11.4%, respectively; reduction of signs of left ventricular hypertrophy- reduction of its posterior wall thickness by 3.2% and 7.5%. The improvement in ECHOCG parameters was accompanied by a decrease in interstitial changes in CT, an improvement in the patency of small and medium bronchi and indicators of lung diffusion, a decrease in the severity of clinical manifestations of CHF, which justifies the use of sartans in the complex therapy of CHF in patients with hypersensitivity pneumonitis combined with coronary artery disease.